Verifying sarcoidosis activity: Chitotriosidase versus ACE in sarcoidosis: A case-control study - Popević Spasoje; Šumarac Zorica; Jovanović Dragana; Babić Dragan; Stjepanović Mihailo; Jovičić Snežana; Šobić-Šaranović Dragana; Filipović Snežana; Gvozdenović Branko; Omčikus Maja; Milovanović Anđela; Videnović-Ivanov Jelica; et al. (Journal of Medical Biochemistry, 2016)
Background: Until now, a proper biomarker(s) to evaluate sarcoidosis activity has not been recognized. The aims of this study were to evaluate the sensitivity and specificity of the two biomarkers of sarcoidosis activity already in use (serum angiotensin converting enzyme - ACE and serum chitotriosidase) in a population of 430 sarcoidosis patients. The activities of these markers were also analyzed in a group of 264 healthy controls. Methods: Four hundred and thirty biopsy positive sarcoidosis patients were divided into groups with active and inactive disease, and groups with acute or chronic disease. In a subgroup of 55 sarcoidosis patients, activity was also assessed by F-18 fluorodeoxyglucose positron emission tomography (18F-FDG-PET) scanning. Both serum chitotriosidase and ACE levels showed non-normal distribution, so nonparametric tests were used in statistical analysis. Results: Serum chitotriosidase activities were almost 6 times higher in patients with active sarcoidosis than in healthy controls and inactive disease. A serum chitotriosidase value of 100 nmol/mL/h had the sensitivity of 82.5% and specificity of 70.0%. A serum ACE activity cutoff value of 32.0 U/L had the sensitivity of 66.0% and the specificity of 54%. A statistically significant correlation was obtained between the focal granulomatous activity detected on 18F-FDG PET/CT and serum chitotriosidase levels, but no such correlation was found with ACE. The levels of serum chitotriosidase activity significantly correlated with the disease duration (P< 0.0001). Also, serum chitotriosidase significantly correlated with clinical outcome status (COS) categories (p = 0.272, P = 0.001). Conclusions: Serum chitotriosidase proved to be a reliable biomarker of sarcoidosis activity and disease chronicity.